Leitura em hospitais: um estudo sobre o uso de e-reader no Hospital das Clínicas da UFMG - Fernanda Riggio (2024)
This research, conducted within a hospital setting, delves into and analyzes the practice of literary and digital literacy among children and adolescents undergoing medical treatment, utilizing an electronic device (e-reader) for reading purposes. It is affiliated with the research project titled ―Digital Literary Reading for Children and Adolescents in Hospitals, a collaborative initiative between the UFMG‘s Faculdade de Letras and the Hospital das Clínicas, conducted from 2021 to 2023. The primary objective was to promote literary engagement within hospital environments, thereby contributing to the physical and mental well-being of hospitalized children. This project draws upon scholarly investigations into reading, literacies, multiliteracies, hospital education, and the impacts of digital technology, particularly the e-reader, within contemporary society. Qualitative field research was undertaken from June to December 2023, involving routine observation and facilitation of literary reading experiences with e- books and digital readers among four children and adolescents admitted to the Pedriatrics ward at UFMG‘s Hospital das Clínicas. Data collection and analysis were conducted through written documentation in a research journal and photographic records, with explicit consent obtained from parents or legal guardians, as well as the patients themselves. Following the mediation of literary reading sessions utilizing e- readers and engaging with the research subjects, noticeable advancements in both literary and digital literacy skills among children and adolescents were observed. The findings indicate that the e-reader: 1) broadens reading opportunities for users, presenting an appealing digital alternative to traditional printed books; 2) allows personalized reading experiences through customizable design, formatting, and brightness settings, thereby allowing adjustments to text presentation for enhanced readability; and 3) fosters the acquisition, expansion, and refinement of technological competencies, thereby promoting digital inclusivity. As an outcome of this research, a reading matrix was formulated for e- reader devices, encompassing the reading and digital competencies of students/patients in hospital settings. This matrix holds potential significance for further research projects that aims to explore the efficacy of e-reader devices for reading in both hospital and educational environments.